Does nuclear power plants affect house prices? : a hedonic price model of Forsmark nuclear power plant - Lokrantz, Malin (SLU/Dept. of Economics, 2014)
Nuclear power plants existences have been well debated since the 70s (Swedish radiation safety authority, 2014). Accidents, risk and presence connected to nuclear power plants have been part of many studies around the world. Recent studies have shown a connection between prices of houses and the distance and presence of nuclear power plant in a surronding area of the house. This paper uses Hedonic price modelling to investigate the willingness to pay for an increased distance to the Swedish nuclear power plant, Forsmark. For the dependent variable selling price was used and the independent variables were number of rooms, living area, other area, lot size, selling year, building year and distance to Forsmark. The findings of the study were a positive relation between distance from Forsmark and house prices within a 25-kilometer range. The study also tested a possible Fukushima effect that prices would go down after the Fukushima accident in 2011. The study didn’t find a statistical Fukushima effect. Further research should be done to look deeper into the effects of having a nuclear power plant in a surrounding area of a house in Sweden. Such research should include more independent variables, observations and also the other nuclear power plants located in Sweden.